Intertextuality, Rhetorical History and the Uses of the Past in Organizational Transition. Issue 12 (December 2018) - Maclean, Mairi; Harvey, Charles; Sillince, John A.A.; Golant, Benjamin D.
This paper draws upon archival and oral history research on organizational transition at Procter & Gamble (1950–2009), during which P&G evolved from a multinational to a global enterprise. Intertextuality, the ways in which texts appropriate prior works to produce new texts, illuminates the practical workings of rhetorical history, accentuating interpretive agency. The uses of the past at P&G involved an authorized historical account relating to socialization, invented tradition, and lessons from past experience, facilitating change within continuity. We show that in transforming from multinational to global enterprise, recognition of the value of history to strategy intensified, engendering rhetorically intense variations on time-honoured themes. Our main contribution to theory is to demonstrate how sensitivity to intertextuality casts light on the nature of organizational history as historically constructed through language, subject to the agency of skilful interpretive actors who engage in intertextual adaptation in pursuit of strategic change as purposes and contexts evolve.